2020
DOI: 10.1111/epi.16572
|View full text |Cite
|
Sign up to set email alerts
|

Deciphering the surgical treatment gap for drug‐resistant epilepsy (DRE): A literature review

Abstract: Patients with drug‐resistant epilepsy (DRE) rarely achieve seizure freedom with medical therapy alone. Despite being safe and effective for select patients with DRE, epilepsy surgery remains heavily underutilized. Multiple studies have indicated that the overall rates of surgery in patients with DRE have stagnated in recent years and may be decreasing, even when hospitalizations for epilepsy‐related problems are on the rise. Ultimately, many patients with DRE who might otherwise benefit from surgery continue t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
31
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(31 citation statements)
references
References 84 publications
0
31
0
Order By: Relevance
“…Epilepsy surgery is currently underutilized despite offering the highest probability of seizure freedom early in a patient's treat-ment journey [24][25][26][27][28][29]. Surgical underutilization could be caused by several factors, from late incorporation into center's treatment algorithms and procedure-related knowledge gaps among HCPs, to a misunderstanding of its risks [14]. As identification of surgical candidacy early in the disease process is essential for better outcomes, it is important for patients to be educated on and evaluated for neurosurgical options early in their epilepsy treatment journey.…”
Section: Ensure Early Treatment and Establish Support Network Upon 1st Seizurementioning
confidence: 99%
See 1 more Smart Citation
“…Epilepsy surgery is currently underutilized despite offering the highest probability of seizure freedom early in a patient's treat-ment journey [24][25][26][27][28][29]. Surgical underutilization could be caused by several factors, from late incorporation into center's treatment algorithms and procedure-related knowledge gaps among HCPs, to a misunderstanding of its risks [14]. As identification of surgical candidacy early in the disease process is essential for better outcomes, it is important for patients to be educated on and evaluated for neurosurgical options early in their epilepsy treatment journey.…”
Section: Ensure Early Treatment and Establish Support Network Upon 1st Seizurementioning
confidence: 99%
“…A multitude of factors could account for why patients have unaddressed DRE, such as gaps in disease education, socioeconomic and societal limitations to healthcare access, lack of care-giver involvement, and healthcare provider (HCP) reluctance to move beyond pharmacological therapies, among others [12,13]. Furthermore, HCP knowledge gaps can lead to underestimations of the damage incurred by DRE and an overestimation of the risks of surgery [14]. These gaps put patients at greater risk of serious adverse clinical events that ultimately contribute to the overuse of healthcare resources [15,16].…”
Section: Introductionmentioning
confidence: 99%
“…Provider preferences, institutional availability, socioeconomics, and factors unique to each clinical case also play a role. 21 , 22) Regardless, once a patient meets the defined criteria for DRE as determined by the American Academy of Neurology (AAN) and International League Against Epilepsy (ILAE), they should be referred to an epilepsy center for further work-up and surgical evaluation. 21 , 23) This is a critical point, as studies have shown an unacceptable and dangerously long 20-year lag between epilepsy diagnosis and surgical referral for adults in the United States.…”
Section: Natural Historymentioning
confidence: 99%
“…However, neither negative MRI, multifocal MRI, nor lack of localizing data from vEEG should result in disqualification from further surgical evaluation. 21) There are multiple non-medical treatment options for treatment of multifocal, generalized epilepsy, and for those with foci in eloquent regions. 22) An appropriate preoperative evaluation that is both comprehensive and germane is essential to achieving the best possible outcomes for all DRE patients.…”
Section: Natural Historymentioning
confidence: 99%
“…6 The community-based integrated care system for the drug-resistant epilepsy has not necessarily worked in each country due to individual situations. 7 Recently, the World Health Organization recognized epilepsy as a major public health concern. 8 The global campaign against epilepsy has been carried out by the World Health Organization, the International League Against Epilepsy, and the International Bureau for Epilepsy.…”
Section: Introductionmentioning
confidence: 99%